THE STRUCTURE OPTIMIZATION AND ANALYSIS OF THE SEMI-AUTOMATIC RAIL-MOUNTED BILATERAL CASTING MACHINE - WANG ChengJun; 3CHEN XiaoZhe; LIU Kai; HUANG RuHang; LI Gang (Jixie qiangdu)
With new semi-automatic rail-mounted bilateral casting machine as the research object,the study is mainly about the light-weight design and mode analysis after the optimization of the concave frame in main bearing parts of the casting machine.At the same time,static analysis of casting machine support system was made. Based on optimization design function of ANSYS Workbench,with total weight of concave frame as target function,total deformation volume as constrain function,section size of each part structure as optimization variable,the study made optimization design for concave frame by modal analysis. The study has reduced vibration and improved work stability. Its working security was determined through stress and deformation analysis of casting ladle support system. The study has also strengthened processing and optimization of its weak part. The casting machine performance has significantly improved after optimization. The process provides a reference for optimal design of casting machinery and other devices.